On the Use of make to vs. make ø in early English Medical Writing - Calle-Martín, Javier; Romero-Barranco, Jesús (My University, 2014)
OBJECT INFINITIVE CONSTRUCTIONS are the most frequent type of non-finite complement clauses, in which the object infinitive may occur either marked (+TO) e.g. to-infinitive or unmarked (-TO) e.g. bare infinitive (Fischer 1992: 316). From a historical point of view, the bare infinitive is found to be the preferred form in Old English, the number of examples being comparatively small though. This picture changed drastically in Middle English, when the to-infinitive outnumbers the bare infinitive in this kind of clause (Visser 1973: 2235). In the early Modern English period, however, both constructions coexisted with the same set of verbs, even though there are conditioning factors triggering the use of a particular type of construction. Among others, the existence of intervening elements between the matrix verb and the object infinitive is found to play a decisive role in the choice of to- or the bare infinitive (Rissanen 1999: 286). The present paper aims to deal with object infinitive constructions in early Modern English with the following three objectives: a) to analyze the use and distribution of marked and unmarked infinitives in the following object-controlling verbs: cause, make, procure, send, entreat, let, suffer, wish, forbid and teach, among others; b) to classify the phenomenon in different text-types; and c) to evaluate if the following factors condition the use of these constructions, i.e. i) the presence of intervening elements between the matrix verb and the object infinitive; ii) the position of the infinitive clause with respect to the matrix clause, whether fronted or not; and iii) the use of coordinated infinitives (Rohdenburg 1996: 156). The data used as source of evidence come from the Electronic Text Edition of Depositions (1560-1760) and the Corpus of Early English Medical Writing, i.e. Early Modern English Medical Texts (EMEMT for the period 1500-1700).
Keywords: Inglés - Sintaxis; Corpus Linguistics; Middle English; Early Modern English; Object Infinitive Constructions